Feed Intake, Body Weight, Average Daily Gain, Feed Conversion Ratio and Carcass Characteristics of Helmeted Guinea Fowl Fed Varying Levels of Phane Meal (Imbrasia belina) as Replacement of Fishmeal under Intensive System - Nobo , G.; Moreki, J.C.; Nsoso, S.J. (International Journal of Poultry Science, 2012)
The objective of this study was to investigate the effect of feeding varying levels of Phane meal (Imbrasia belina) as a protein source on feed intake, body weight, average daily gain, feed conversion ratio and carcass characteristics of guinea fowl under intensive system up to 13 weeks of age. A total of 96 day old keets were randomly allocated to 4 treatment diets, which were replicated 4 times (n = 6/replicate). Dietary inclusion levels of Phane meal were 4.5%, 9% and 13.5% while control diet contained 3% fishmeal. Parameters measured were Feed Intake (FI), Body Weight (BW) and carcass dressed weight, Average Daily Gain (ADG), dressing percentage, Feed Conversion Ratio (FCR), carcass dressed weight and dressing percentage. The present results showed that FI increased significantly (p<0.05) with age. Dietary treatment did not affect FI. There was no significant difference for ADG among treatments, however, guinea fowl fed control diet had higher ADG (0.0138±0.0003 kg) and lower FCR (3.83) than birds on 4.5% Phane diet which had FCR of 4.09. Body weight increased significantly (p<0.05) with age. However, dietary treatment had no significant effect on BW at week 13 (slaughter age). Birds on control diet had significantly higher carcass dressed weight compared to other treatments. Female and male birds fed control diet had significantly higher dressing percentage (75.82±2.99 and 74.10±2.99%, respectively) compared to other treatments but dressing percentage of female and male birds on 4.5% Phane diet did not differ. These results suggested that Phane meal can be included in guinea fowl diets up to 4.5% without affecting growth.